Tengku Anis Library UiTM Machang / Nur Najihah Haris Fadila - Haris Fadila, Nur Najihah (Tengku Anis Library Uitm Machang, 2021)
This paper includes a detailed about the industrial traning that is being conducted at Perpustakaan Tengku Anis, UiTM Machang Kelantan. Based on the time periodfrom 6 September 2021 until 6 February 2022. The chapter is divided into four chapters: an introduction to UiTM Machang and Tengku Anis Library, differences in roles and job scopes performed by fourdepartments at Tengku Anis Library, activities performed during practical traning and special project management,and knowledge and lesson learned during the traning period.